2021
DOI: 10.30880/jamea.2021.02.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Backpressure in Exhaust Muffler for Automobile

Mohd Kamal Hamid,
Siti Marhamah Rosman,
Norliana Muslim

Abstract: The goal of this study is to optimise the exhaust middle box muffler of an automobile by focusing on the design of the perforated pipes. Back pressure and pressure drop in the exhaust are two characteristics that contribute to the various effects of an internal combustion engine. In this study, the pressure distribution of an existing exhaust middle box muffler on the perforated pipe is evaluated using Computational Fluid Dynamic (CFD) software, and the suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Kamal et al (2021) state that the larger distance between perforations at 20 mm for exhaust muffler leads to considerable disparities in the results, with a 15% difference in pressure drop, as opposed to the smaller distance between perforations, which results in less than 1% difference in pressure drop for perforated pipes with 6mm and 7mm diameters. The perforation diameter of 5mm in exhaust muffler resulted in a pressure decrease of up to 44.66% [11]. From the study, it can be observed that the bending angle and radius of an exhaust pipe have a significant impact on engine backpressure.…”
Section: Figure 1 Components Of An Exhaust Systemmentioning
confidence: 89%
“…Kamal et al (2021) state that the larger distance between perforations at 20 mm for exhaust muffler leads to considerable disparities in the results, with a 15% difference in pressure drop, as opposed to the smaller distance between perforations, which results in less than 1% difference in pressure drop for perforated pipes with 6mm and 7mm diameters. The perforation diameter of 5mm in exhaust muffler resulted in a pressure decrease of up to 44.66% [11]. From the study, it can be observed that the bending angle and radius of an exhaust pipe have a significant impact on engine backpressure.…”
Section: Figure 1 Components Of An Exhaust Systemmentioning
confidence: 89%